Fishing Down the North Sea - HOLM, POUL (Universitatsverlag Gottingen, 2010)
Historical and archaeological research has fundamentally changed our knowledge of past abundance and distribution of North Sea marine animal populations in the past ten years. We may now contrast current populations to historical baselines and we are beginning to understand the dynamics and drivers of the system to a degree which was previously unthinkable. While our understanding of the past benefits from this progress, the main contribution to the future may be to fisheries managers.
Beitrage zum Gottinger Umwelthistorischen Kolloquium 2007 - 2009.
PUBLISHED
Gottingen, Germany
Keywords: fishing; north sea